Screening of Malaysian Medicinal/Herbs and Aquatic Plants for Pancreatic Lipase Inhabitory Activities and Identification of Active Constituent - Ado, Muhammad Abubakar (2010)
The compounds that help to slow down the digestion of triacylglycerols inside pancreatic and small intestine of human play an important role in the control of obesity. In this study the effects of 80% methanol extracts of different parts (seeds, fruits, leaves, flowers,roots) of some medicinal/herbals and aquatic plants for their anti-lipase activity was determined. The effect of each plant extract on porcine pancreatic lipase was measured based on titrimetric method. The results revealed of the one hundred (100) plant samples screened, eighty eight (88) of the extracts were observed to inhibit while twelve (12) were found to promote the activity and only two extracts did not show any activity on the enzyme. Four of the plant extracts Archidendron jiringa (Jack) I.C Nielsen, Averrhoe carambola L. Cynometra cauliflora and Alevrites moluccana (L.) Willd have shown the highest anti-lipase activity of 100%, and twenty one (21) extracts observed to have high activity above 70%. Eighteen (18) out of these twenty one (21) have anti-lipase activity of greater than 80%. Thirteen (13) have presented moderate inhibition with a high proportion of 62% exhibited lower inhibition. Twenty nine (29) extracts out of these (86)can be regarded as very poor inhibitors, as their percent inhibition was less than 20% and only 1.74% was shown to have no inhibitory activity. In the process of isolating the active compounds, liquid-liquid partitioning of the crude methanolic extract of Cynometra cauliflora leaves was carried out. Five different fractions hexane, DCM,EtOAc, n-BuOH and aqueous was obtained. All the fractions were tested for anti-lipase activity and the active components reside manily in ethyl acetate fraction. The isolation and identification of active compounds from the most active fraction (ethyl acetate) was further fractionated using silica gel column chromatography (normal phase). The active fraction was further purified by the use of Sephadex LH-20 chromatography. The structure of the active compound from ethyl acetate fraction of Cynometra cauliflora was found to be kaempferol-3-O-rhamnoside. The structure of this active compound was identified from spectroscopic data analysis of IR, MS, 1H NMR, 13C NMR and 2D-NMR.